The Convention on the Elimination of All Forms of Discrimination against Women and its Optional Protocol (2003)
The handbook presents the background to and content of the Convention and the Optional Protocol. It describes the role of the Committee on the Elimination of Discrimination against Women, the treaty body established by the Convention to secure implementation at the national level. The Handbook also focuses on what parliamentarians can do to ensure effective implementation of the Convention and encourage use of the Protocol. It seeks to encourage parliamentarians to take measures to ensure that national laws, policies, actions, programmes and budgets reflect the principles and obligations in the Convention.